2022
DOI: 10.1097/icu.0000000000000881
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in dementia

Abstract: Purpose of reviewArtificial intelligence tools are being rapidly integrated into clinical environments and may soon be incorporated into dementia diagnostic paradigms. A comprehensive review of emerging trends will allow physicians and other healthcare providers to better anticipate and understand these powerful tools. Recent findingsMachine learning models that utilize cerebral biomarkers are demonstrably effective for dementia identification and prediction; however, cerebral biomarkers are relatively expensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The development of AI, coupled with the utility of retinal imaging, could potentially be the answer to this difficult conundrum [ 69 ]. Using eye-based ML models for dementia identification has several advantages, including low cost, easy acquisition, and the non-invasive feature, which make retinal tests suitable for large-scale population screening and investigations of preclinical AD [ 70 ]. In one study, in an internal validation dataset, a DL model was found to have an accuracy of 83.6% (SD 2.5), a sensitivity of 93.2% (SD 2.2), a specificity of 82.0% (SD 3.1), and an AUROC of 0.93 (0.01) for the detection of AD.…”
Section: Retina Photo-based Ai In Non-ophthalmic Disordersmentioning
confidence: 99%
“…The development of AI, coupled with the utility of retinal imaging, could potentially be the answer to this difficult conundrum [ 69 ]. Using eye-based ML models for dementia identification has several advantages, including low cost, easy acquisition, and the non-invasive feature, which make retinal tests suitable for large-scale population screening and investigations of preclinical AD [ 70 ]. In one study, in an internal validation dataset, a DL model was found to have an accuracy of 83.6% (SD 2.5), a sensitivity of 93.2% (SD 2.2), a specificity of 82.0% (SD 3.1), and an AUROC of 0.93 (0.01) for the detection of AD.…”
Section: Retina Photo-based Ai In Non-ophthalmic Disordersmentioning
confidence: 99%
“…33 For a long time, the retina has been considered a potential candidate for detecting neurodegenerative conditions, due to its high similarity and connections to the brain. 34,35 Similar to the brain, the retina is affected by ageing and neurodegenerative processes. However, a crucial question would be whether the pathological ageing of the retina reflects the nature and amount of associated brain lesions, especially in patients with dementia.…”
Section: Alzheimer's Disease and Dementiamentioning
confidence: 99%
“…To our knowledge, this is the first publication specifically reviewing LLMs in the context of dementia management and care. Previous reviews surveyed AI in dementia more broadly (de la Fuente Garcia et al, 2020 ; Lee et al, 2021 ; Richardson et al, 2022 ; Borchert et al, 2023 ; Tsoi et al, 2023 ) or focused on AI for prediction and early diagnosis (Stamate et al, 2020 ; Li et al, 2022 ; Merkin et al, 2022 ; Borchert et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%